Hollywood rules - Schmedders, Karl; Snyder, Charlotte; Schaedel, Ute ([London] : SAGE, 2016)
Wall Street hedge fund manager Kim Meyer is considering investing in an SFA (slate financing arrangement) in Hollywood. Dave Griffith, a Hollywood producer, is pitching for the investment and has conducted a broad analysis of recent movie data to determine the important drivers of a movie's success. In order to convince Meyer to invest in an SFA, Griffith must anticipate possible questions to maximize his persuasiveness.
Originally Published in: Schmedders, K., Snyder, C., & Schaedel, U. (2011). Hollywood Rules (case revised 08/11/2012). 5-111-012. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Investment analysis -- Case studies; Marketing research -- Case studies